A directionally solidified Fe-B-Si alloy surface protective film and preparation method thereof
Fe-B-Si alloy is prepared through a directional solidification process, and a three-layer tenon structure protective film is formed in the zinc liquid, which solves the serious cavitation problem of steel materials in the hot-dip galvanizing production line and realizes the alloy at high flow rate zinc liquid High-efficiency corrosion resistance in the
Patent Information
- Application Number
- CN202310070464.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-17
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-01-17
AI Technical Summary
In the hot-dip galvanizing production line, steel materials have severe cavitation in liquid zinc, and existing anti-cavitation materials have high cost and poor performance, which cannot effectively solve this problem.
The Fe-B-Si alloy was prepared by a directional solidification process and interfacial reaction was carried out in the zinc liquid to form a three-layer Si-rich layer/FeZn10/FeZn13 protective film with a mortise and tenon structure, enhancing the alloy's anti-zinc liquid cavitation performance.
By forming a dense three-layer protective film that is closely linked to the alloy, the cavitation of the zinc liquid on the alloy is significantly reduced, and the corrosion resistance of Fe-B-Si alloy in high-flow zinc liquid is improved.
Smart Images

Figure CN116121680B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of zinc liquid corrosion resistance of hot-dip galvanizing engineering equipment, and particularly relates to a directionally solidified Fe-B-Si alloy surface protective film and a preparation method thereof. Background Art
[0002] Metal corrosion has caused enormous losses to my country's economic and industrial development. The economic losses and safety issues caused by cavitation erosion in flowing media cannot be underestimated. Hot-dip galvanizing is the most widely used metal corrosion protection process, offering advantages such as low cost and high efficiency. However, in continuous hot-dip galvanizing production lines, key components such as sinking rollers and stabilizing rollers are immersed in high-temperature components for long periods of time, subjecting them to intense corrosion from liquid zinc. This seriously impacts the quality of the production line's equipment and results in significant economic losses. Different components in hot-dip galvanizing production lines experience varying levels of damage. The primary damage type for shaft parts is corrosive wear, while the surface of rollers is primarily subject to localized erosion and cavitation.
[0003] Cavitation, also known as bubble corrosion, refers to the vaporization of a corrosive liquid to form bubbles when the local pressure drops in a high-speed flowing liquid. When the bubbles enter the high-pressure area with the liquid flow, they collapse and produce high-speed microjets and shock waves, which repeatedly hit the surface of the flow-through components and cause damage. There are currently three solutions to cavitation: one is to reduce cavitation by optimizing the shape of the components; the second is to develop new cavitation-resistant materials; and the third is to prepare a protective layer with excellent cavitation resistance on the surface of the substrate. The development of new cavitation-resistant materials, such as high-temperature alloys and ceramic materials, is costly and the materials themselves are brittle, resulting in low economic benefits. The coating material's bonding ability is weakened under the scouring effect of high-speed, high-temperature zinc liquid, and the coating is prone to peeling off. Currently, none of these solutions can effectively solve the cavitation problem of hot-dip galvanizing production line engineering equipment.
[0004] The most commonly used component material in the hot-dip galvanizing process is steel. However, due to the Sandelin effect, steel with a certain silicon content will undergo a violent reaction between iron and zinc during hot-dip galvanizing, producing a coating with a dull surface and poor adhesion. The high-energy cavitation generated by the high-temperature zinc liquid strongly impacts the coating, causing severe surface peeling. On the one hand, this leads to increased zinc consumption, and on the other hand, the loss of components also increases equipment maintenance costs. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a directionally solidified Fe-B-Si alloy surface protective film and a preparation method thereof in view of the deficiencies in the above-mentioned prior art, so as to solve the technical problem of severe cavitation of steel materials in liquid zinc.
[0006] The present invention adopts the following technical solutions:
[0007] A method for preparing a surface protective film of a directionally solidified Fe-B-Si alloy comprises the following steps:
[0008] The Fe-B-Si alloy prepared by directional solidification process is placed in liquid zinc for interfacial reaction. After the reaction is completed, it is cooled to obtain the Fe-B-Si alloy with a three-layer mortise and tenon structure protective film.
[0009] Specifically, the Fe-B-Si alloy includes, by weight percentage, 0.13-0.22% C, 2.05-3.55% B, 0.75-0.82% Cr, 2.42-2.58% Si, and the rest being Fe and inevitable trace impurities.
[0010] Specifically, the melting temperature of the directional solidification process is 1570-1640°C, and the casting temperature is 1420-1450°C.
[0011] Specifically, the directional solidification cooling rate is 10.2-15.6°C / s, and the undercooling degree is 95-100°C.
[0012] Specifically, the boride growth orientation of the directionally solidified Fe-B-Si alloy is in the
[002] direction, with an angle of 90° to the corrosion interface.
[0013] Specifically, the temperature of the interface reaction is 460-470° C., the rotation speed of the Fe-B-Si alloy is controlled to be 300 r / min, and the reaction time is 2-10 h.
[0014] Furthermore, the interface reaction is specifically as follows: the surface of the directionally solidified Fe-B-Si alloy is corroded and Si element enrichment is generated, forming a Si-rich surface film between the Fe2B skeleton; the Fe atoms in the Si-rich surface film further diffuse and react with the high-temperature liquid zinc to form a columnar ζ-FeZn 13 protective film; subsequently generated ζ-FeZn 13 The protective film reacts with the Si-rich layer to form a layer of δ-FeZn between the two layers and between the Fe2B skeleton. 10 Protective film, δ-FeZn 10 The protective film grows like a tree root; eventually, a Si-rich layer / FeZn layer is formed on the surface of the iron-boron alloy. 10 / FeZn 13 The three layers of nested composite films form a mortise and tenon structure with the Fe2B skeleton, forming a composite protective film on the surface of the Fe-B-Si alloy that resists zinc liquid cavitation erosion.
[0015] Specifically, the thickness of the three-layer mortise and tenon structure protective film is 48.0 to 109.7 μm.
[0016] Furthermore, the innermost layer of the three-layer mortise and tenon structure is a Si-rich layer, and the FeZn 10 / FeZn 13layer, the thickness of the Si-rich layer is 3.9 to 6.5 μm, FeZn 10 / FeZn 13 The thickness of the layer is 44.1 to 103.2 μm.
[0017] Another technical solution of the present invention is a directionally solidified Fe-B-Si alloy surface protective film, wherein the cavitation rate of the protective film is 4.01 to 6.76 μm / h.
[0018] Compared with the prior art, the present invention has at least the following beneficial effects:
[0019] The present invention discloses a method for preparing a surface protective film of a directionally solidified Fe-B-Si alloy. After the ingredients are mixed, a sample is prepared using a directional solidification technique to obtain an oriented boride skeleton. A certain amount of pure zinc is weighed and placed in a zinc liquid corrosion device to be completely melted. The sample is fixed on the sample clamp of the zinc liquid corrosion device with a clamp, 35 mm away from the center, to prevent the sample from being moved by the impact of the zinc liquid. The temperature in the furnace is maintained, and the motor drives the sample to rotate at a speed of 300 r / min. After the formation time of the protective film is reached, the sample with the protective film grown on the surface is taken out and slowly cooled to room temperature. Through detection and characterization, comprehensive information such as the specific composition, morphology, and thickness of the protective film is obtained. The Si-rich layer / FeZn prepared by this method 10 / FeZn 13 The three-layer self-grown high-density composite anti-cavitation film produces a strong pinning effect with the sample, and is interlocked with the oriented boride skeleton layer by layer to form a mortise and tenon structure. It has a strong adhesion bond with the alloy and isolates the direct contact with the outer layer of high-flow zinc liquid, weakening the high-energy impact of cavitation collapse on the alloy, reducing the spalling of the alloy under cavitation, and greatly improving the anti-cavitation performance of Fe-B-Si alloy in flowing liquid metal zinc.
[0020] Furthermore, steel is the most widely used material in the hot-dip galvanizing industry. Directionally solidified Fe-B-Si alloy can produce a boride skeleton with consistent orientation and regular arrangement, which can play a strong pinning role on the subsequent self-grown protective film; its composition characteristics are mainly due to the increased content of Si elements, which is conducive to the rapid formation of the inner Si-rich protective film, inhibiting the mutual diffusion of iron elements in the inner alloy and zinc elements in the outer high-flow zinc liquid, and promoting the formation of a smoother FeZn 13 Phase, so that the thickness of the protective film is increased. At the same time, the strongly oriented boride can regulate the morphology of the outer protective layer, so that it forms a regular columnar mortise and tenon structure, which is interlocked layer by layer and strengthens the pinning effect between the outer layer and the boride.
[0021] Furthermore, the melting temperature of the directional solidification process is 1570-1640°C to ensure that the raw materials are quickly and fully melted and the alloy elements are evenly distributed; the casting temperature is 1420-1450°C to reduce the superheat of the molten metal, so that the molten metal solidifies quickly, reduce the segregation of alloy elements during the solidification process, and reduce the composition unevenness of the casting.
[0022] Furthermore, the directional solidification cooling rate is 10.2-15.6°C / s, and the undercooling degree is 95-100°C, which ensures that a directional structure with regular arrangement and consistent orientation is generated during the orientation of the alloy.
[0023] Furthermore, the boride growth orientation of the directionally solidified Fe-B-Si alloy is in the
[002] direction, with an angle of 90° to the corrosion interface. After the alloy is cavitated, one end of the boride is embedded in the matrix, and the other end extends into the product, fixing the product so that in the subsequent process, the product is firmly embedded with the boride and tightly connected to the matrix, presenting a mortise and tenon-like connection.
[0024] Furthermore, the temperature of the interface reaction is 460-470°C, the rotation speed of the Fe-B-Si alloy is controlled to be 300 r / min, and the reaction time is 2-10 h, simulating the service conditions of hot-dip galvanizing in actual working conditions to form a protective film with a certain thickness.
[0025] Furthermore, the products formed by the interfacial reaction of the directionally solidified Fe-B-Si alloy in the high-flow zinc liquid grow naturally and adhere tightly to the alloy surface, preventing further corrosion.
[0026] Furthermore, a high-density and high-bonding-strength three-layer composite protective film with a thickness of 48.0 to 109.7 μm is formed for Fe-B-Si alloy in hot-dip galvanizing process to resist zinc liquid cavitation. This protective film has four protective effects on the alloy: First, the inner silicon-rich layer protective film is formed quickly, while promoting the outer FeZn 13 Rapid formation inhibits the mutual diffusion of iron and zinc, and improves the cavitation resistance of the alloy; secondly, the protective film formed isolates the alloy from direct contact with the zinc liquid, to a certain extent blocks the penetration and corrosion of the zinc liquid on the alloy, and inhibits the cavitation corrosion of the alloy; thirdly, the strongly oriented boride regulates the outer layer FeZn 13 morphology, forming a "root effect", forming a mortise and tenon structure, and interlocking with the oriented boride layer by layer, so that the protective film and the alloy interface are firmly pinned, thereby inhibiting the shedding of the protective film; fourth, the three-layer protective film has the characteristics of a three-layer composite protective film that can self-grow from liquid flowing metal zinc with strong bonding force and high density, effectively realizing the self-repair and self-growth characteristics of the protective film during service.
[0027] Furthermore, the inner Si-rich protective film is densely, continuously and smoothly bonded to the substrate, inhibiting diffusion, stabilizing the interface layer and stabilizing the thickness of the outer ζ-FeZn13 protective film, becoming the third barrier to prevent zinc liquid from corroding the alloy. The thickness of the inner Si-rich protective film is 3.9 to 6.5 μm, which is at the micron level and well connected to the outer FeZn 10 / FeZn 13 The protective film is tightly bonded to the alloy, becoming a barrier to prevent zinc liquid from corroding the alloy. The outer layer of FeZn 10 / FeZn 13 The double-layer protective film is continuously bonded to the inner layer, with a smooth interface and good adhesion without cracks. It is interlocked with the boride skeleton and arranged alternately in a mortise and tenon structure. It has a stable bond with the alloy interface and can effectively prevent the protective film from peeling off due to the high-energy impact of cavitation collapse in high-flow zinc liquid. 10 / FeZn 13 The protective film has a stable thickness and dense structure. The double-layer protective film isolates the direct contact between the alloy and the zinc liquid to a large extent, preventing the zinc liquid from cavitating the alloy. 10 / FeZn 13 The thickness of the double-layer protective film is 44.1 to 103.2 μm. When the cavitation time is 2 hours, the thickness of the double-layer protective film is 44.1 μm, when the time is 4 hours, the thickness is 66.9 μm, when the time is 6 hours, the thickness is 77.3 μm, when the time is 8 hours, the thickness is 85.6 μm, and when the time is 10 hours, the thickness is 103.2 μm. The double-layer film provides a double-layer protective barrier, isolating the alloy from the zinc liquid, and largely preventing the zinc liquid from corroding the alloy.
[0028] In summary, the surface film formed by the present invention forms a mortise and tenon structure with the metal substrate, which is firm and has high stability and density. It can effectively prevent surface peeling caused by zinc liquid cavitation, and provides a solution to the problem of serious cavitation damage to parts in the hot-dip galvanizing process.
[0029] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a schematic diagram of the zinc liquid corrosion device;
[0031] Figure 2 This is the SEM image of the cross section of the sample taken out after 10 hours;
[0032] Figure 3 This is the graph showing the thickness change of protective film at different corrosion times;
[0033] Figure 4 is the graph of corrosion rate changing with time;
[0034] Figure 5 SEM and elemental EDS images of the sample and its protective film.
[0035] Among them, 1. stirring motor; 2. motor bracket; 3. furnace cover; 4. sample rack; 5. fixture; 6. sample; 7. crucible; 8. molten zinc; 9. vibration platform; 10. vibration machine; 11. shock absorption device; 12. heating furnace; 13. guide column; 14. handwheel; 15. reducer. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be described clearly and completely below. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. All other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0037] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0038] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0039] In the present invention, unless otherwise specified, percentages (%) or parts refer to percentages by weight or parts by weight relative to the composition.
[0040] In the present invention, unless otherwise specified, the components involved or their preferred components can be combined with each other to form a new technical solution.
[0041] In this disclosure, unless otherwise specified, the numerical range "a-b" is an abbreviation for any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "6-22" indicates that all real numbers between "6-22" are listed herein, and "6-22" is merely an abbreviation for these numerical combinations.
[0042] The "range" disclosed in the present invention is in the form of lower limit and upper limit, which can be one or more lower limits, and one or more upper limits respectively.
[0043] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0044] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the order. Preferably, the reaction method herein is carried out sequentially.
[0045] Unless otherwise indicated, the professional and scientific terms used herein are the same as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content can also be applied to the present invention.
[0046] The present invention provides a surface protective film of a directionally solidified Fe-B-Si alloy and a preparation method thereof. The method comprises placing the directionally solidified Fe-B-Si alloy in a flowing zinc liquid at 460-470°C, placing the sample on a sample holder of a zinc liquid corrosion device and rotating the sample with a motor to move the sample relative to the zinc liquid for 2-10 hours, and producing a three-layer Si-rich layer / FeZn layer on the surface of the sample that is resistant to high-flow liquid zinc cavitation. 10 / FeZn 13 Protective film. Three layers of Si-rich layer / FeZn 10 / FeZn 13 The protective film significantly inhibits the interdiffusion of iron and zinc, isolating the alloy from contact with liquid zinc and reducing cavitation corrosion. The film's dense structure, strong adhesion to the substrate, and smooth interface interlock with the boride skeleton, forming an alternating mortise and tenon structure. This significantly reduces spalling and provides an effective protection against severe cavitation corrosion in hot-dip galvanizing parts.
[0047] The present invention provides a method for preparing a surface protective film on a directionally solidified Fe-B-Si alloy. The method comprises placing the prepared directionally solidified Fe-B-Si alloy in a flowing zinc solution to in-situ generate a protective film. The specific steps are as follows:
[0048] S1. Preparing an Fe-B-Si alloy by directional solidification, wherein the alloy comprises 0.13-0.22% C, 2.05-3.55% B, 0.75-0.82% Cr, 2.42-2.58% Si, and the remainder Fe and unavoidable trace impurities;
[0049] The smelting temperature is 1570-1640℃, which is higher than the melting point of pure iron 1534℃, so that various raw materials can be melted quickly to ensure that the molten steel is fully stirred and melted by heat flow, and to ensure the melt quality for melt purification.
[0050] The casting temperature is 1420-1450°C, which is higher than the liquidus temperature of the Fe-B alloy phase diagram of 1381°C. It maintains a certain degree of superheat and good fluidity, ensuring the quality of the casting.
[0051] The cooling rate of the directional solidification process is 10.2-15.6°C / s, and the undercooling degree is 95-100°C.
[0052] After cooling to room temperature and solidifying, the boride growth orientation of the directionally solidified Fe-B alloy is in the
[002] direction, with an angle of 90° to the corrosion interface.
[0053] S2. Cut the directionally solidified Fe-B alloy into several 120*10*4mm pieces along the direction of directional solidification. 3 The test samples were then ground with a grinder and ultrasonically cleaned to remove wire cutting marks and oil stains.
[0054] S3. Place 10 kg of pure zinc into the zinc liquid corrosion device, set the program to raise the furnace temperature to 460-465°C, and keep it warm for 120 minutes to completely melt the pure zinc;
[0055] S4. Fix the treated test sample vertically in the fixture at a distance of 35 mm from the center. Set the program to keep the zinc liquid temperature at 460-470°C and the motor to drive the sample to rotate at a speed of 300 r / min for 2-10 hours.
[0056] S5. After the time requirement is met, the test sample is taken out and placed to cool to room temperature. The thickness of the three-layer high-density mortise and tenon structure composite protective film for directionally solidified iron-boron alloy resistant to liquid zinc cavitation erosion is finally formed, which is 48.0 to 109.7 μm;
[0057] The innermost Si-rich protective film of the three-layer high-density mortise and tenon structure composite protective film is densely, continuously and smoothly bonded to the substrate, inhibiting diffusion, stabilizing the interface layer and stabilizing the outer FeZn 10 / FeZn 13 Double layer protective film thickness.
[0058] FeZn outer layer 10 / FeZn 13 The double-layer protective film is continuously combined with the inner layer, with a smooth interface, good adhesion and no cracks, and is interlocked with the boride skeleton, alternating and arranged in a mortise and tenon structure. 10 / FeZn 13 The double-layer protective film is stable and dense in thickness.
[0059] The innermost Si-rich protective film has a thickness of 3.9 to 6.5 μm, and the outer FeZn 10 / FeZn 13 The thickness of the double-layer protective film is 44.1 to 103.2 μm.
[0060] The inner layer of the three-layer, high-density mortise and tenon composite protective film is dense and tightly adheres to the substrate, inhibiting the diffusion of zinc and iron. The outer layer forms a root structure that interlocks with the boride, creating a tight fit. The protective film and alloy form a three-layer mortise and tenon structure, with each layer providing strong protection and reinforcement, thus inhibiting the shedding of surface products and providing excellent resistance to zinc cavitation corrosion.
[0061] S6. Test and characterize the performance, material type, thickness, density, etc. of the protective film.
[0062] S601. Observe the morphology of the protective film formed on the surface of the alloy immersed in the zinc solution, and evaluate the ability of the protective film formed in the flowing zinc solution to improve the cavitation corrosion resistance of the Fe-B-Si alloy. A three-layer protective film is formed on the surface of the Fe-B-Si alloy immersed in the zinc solution, which is well bonded to the alloy and forms a mortise and tenon structure with each other. This three-layer protective film not only inhibits the mutual diffusion of iron and zinc, but also blocks the cavitation corrosion of the high-velocity liquid zinc, thereby improving the cavitation corrosion resistance of the Fe-B-Si alloy in high-velocity liquid zinc.
[0063] S602. Cold-mount the sample with epoxy resin, prepare the interface metallographic sample, and characterize the morphology of the interface protective film by SEM and EPMA.
[0064] After the sample was cold mounted with epoxy resin, it was polished in parallel to the interface using 600#, 800#, 1000#, and 1200# SiC water sandpaper in sequence until the interface was visible, and then polished with diamond polishing agent and canvas to prevent the interface from being damaged by human factors.
[0065] A field emission scanning electron microscope (model GeminiSEM 500) and an energy dispersive spectrometer (EDS) were used to observe the specific morphology of the protective film and detect and analyze the composition of the protective film. The material of the protective film was confirmed by the atomic ratio of Fe, Zn and Si.
[0066] The invention discloses a directionally solidified Fe-B-Si alloy surface protective film. The protective film has a cavitation rate of 4.01 to 6.76 μm / h, solves the problem of severe cavitation of the Fe-B alloy in flowing zinc liquid, and improves the cavitation resistance of the Fe-B alloy to liquid metal in the presence of flowing liquid metal.
[0067] The present invention takes into account various unfavorable factors caused by the development of new materials and coatings, combines the advantages of chemical reactions, and uses the reaction of liquid zinc and iron to generate a three-layer protective film on the surface of the directionally solidified Fe-B alloy for the first time, which improves the resistance of the Fe-B alloy to zinc liquid cavitation.
[0068] The protective film prepared by the present invention has a three-layer Si-rich layer / FeZn mortise and tenon structure. 10 / FeZn 13 The protective film can inhibit the diffusion of iron and zinc atoms, has a dense structure, a smooth surface, and is interlocked with the oriented borides in the alloy to form a mortise and tenon structure. The tight combination, on the one hand, slows down the corrosion of the alloy by high-flow zinc liquid, and on the other hand, largely ensures the bonding ability between the film and the substrate, reduces the problem of spalling, and realizes the Fe-B-Si alloy's resistance to high-flow zinc liquid cavitation erosion.
[0069] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0070] Example 1
[0071] Preparation of Surface Protective Film on Fe-B-Si Alloy Resistant to Cavitation Erosion by High-Flow Zinc Liquid
[0072] The present invention selects pig iron, low-carbon ferrochrome, ferroboron, industrial pure iron and ferrosilicon alloy as raw materials.
[0073] 1) An Fe-B alloy was prepared by directional solidification. The composition of the Fe-B alloy, by weight, was 0.13% C, 2.05% B, 0.75% Cr, and 2.42% Si, with the remainder being Fe and unavoidable trace impurities. The alloy was prepared at a melting temperature of 1570°C, a casting temperature of 1420°C, a directional solidification cooling rate of 10.2°C / s, and a supercooling of 95°C. The Fe-B-Si alloy had a boride growth orientation in the
[002] direction.
[0074] 2) Cut the directionally solidified Fe-B-Si alloy into 120*10*4mm pieces along the direction of directional solidification 3 The test sample is then ground with a grinder and ultrasonically cleaned to remove wire cutting marks and oil stains on the sample;
[0075] 3) Place 10 kg of pure zinc into the zinc liquid corrosion device, set the program to raise the furnace temperature to 460°C, and keep it at this temperature for 120 minutes to completely melt the pure zinc;
[0076] 4) Fix the treated test sample vertically on the sample clamp of the zinc liquid corrosion device, 35mm away from the center. The device diagram is as follows Figure 1 As shown in the figure, the program is set to keep the zinc liquid temperature at 460℃, and the motor drives the sample 6 to rotate at a speed of 300r / min for 2h. Through the cross-sectional sample preparation, it can be observed that the three layers of Si-rich layer / FeZn generated in situ 10 / FeZn 13 The protective film thickness is 48.0 μm.
[0077] Example 2
[0078] Preparation of Surface Protective Film on Fe-B-Si Alloy Resistant to Cavitation Erosion by High-Flow Zinc Liquid
[0079] The present invention selects pig iron, low-carbon ferrochrome, ferroboron, industrial pure iron and ferrosilicon alloy as raw materials.
[0080] 1) An Fe-B alloy was prepared by directional solidification. The composition of the Fe-B alloy, by weight, was 0.16% C, 2.32% B, 0.77% Cr, and 2.47% Si, with the remainder being Fe and unavoidable trace impurities. The alloy was prepared at a melting temperature of 1582°C, a casting temperature of 1433°C, a directional solidification cooling rate of 11.3°C / s, and an undercooling of 98°C. The Fe-B-Si alloy had a boride growth orientation in the
[002] direction.
[0081] 2) Cut the directionally solidified Fe-B-Si alloy into 120*10*4mm pieces along the direction of directional solidification 3 The test sample is then ground with a grinder and ultrasonically cleaned to remove wire cutting marks and oil stains on the sample;
[0082] 3) Place 10 kg of pure zinc into the zinc liquid corrosion device, set the program to raise the furnace temperature to 462 ° C, and keep it at this temperature for 120 minutes to completely melt the pure zinc;
[0083] 4) The treated test sample was fixed vertically on the sample holder of the zinc liquid corrosion device at a distance of 35mm from the center. The program was set to keep the zinc liquid temperature at 462℃ and the motor drove the sample to rotate at a speed of 300r / min for 4h. Through the cross-sectional sample preparation, the in-situ generated three-layer Si-rich layer / FeZn 10 / FeZn 13 The thickness of the protective film is 71.3 μm.
[0084] Example 3
[0085] Preparation of Surface Protective Film on Fe-B-Si Alloy Resistant to Cavitation Erosion by High-Flow Zinc Liquid
[0086] The present invention selects pig iron, low-carbon ferrochrome, ferroboron, industrial pure iron and ferrosilicon alloy as raw materials.
[0087] 1) A Fe-B-Si alloy was prepared by directional solidification. The composition of the iron-boron alloy, by weight, was 0.17% C, 2.74% B, 0.80% Cr, and 2.51% Si, with the remainder being Fe and unavoidable trace impurities. The alloy was prepared at a melting temperature of 1598°C, a casting temperature of 1438°C, a directional solidification cooling rate of 12.5°C / s, and an undercooling of 96°C. The boride growth orientation of the Fe-B-Si alloy was
[002] .
[0088] 2) Cut the directionally solidified Fe-B-Si alloy into 120*10*4mm pieces along the direction of directional solidification 3 The test samples were then polished with a grinder and ultrasonically cleaned to remove wire cutting marks and oil stains on the samples.
[0089] 3) Place 10 kg of pure zinc into the zinc liquid corrosion device, set the program to raise the furnace temperature to 465 ° C, and keep it at this temperature for 120 minutes to completely melt the pure zinc;
[0090] 4) The treated test sample was fixed vertically on the sample holder of the zinc liquid corrosion device at a distance of 35mm from the center. The program was set to keep the zinc liquid temperature at 465℃, the motor drove the sample to rotate at a speed of 300r / min, and the sample moved at a speed of 7500mm / mm relative to the zinc liquid for 6 hours. Through the cross-sectional sample preparation, the in-situ generated three-layer Si-rich layer / FeZn 10 / FeZn 13 The thickness of the protective film is 82.8 μm.
[0091] Example 4
[0092] Preparation of Surface Protective Film on Fe-B-Si Alloy Resistant to Cavitation Erosion by High-Flow Zinc Liquid
[0093] The present invention selects pig iron, low-carbon ferrochrome, ferroboron, industrial pure iron and ferrosilicon alloy as raw materials.
[0094] 1) A Fe-B-Si alloy was prepared by directional solidification, wherein the composition of the iron-boron alloy, by weight, included 0.21% C, 3.38% B, 0.80% Cr, and 2.55% Si, with the remainder being Fe and unavoidable trace impurities. The alloy was prepared at a melting temperature of 1623°C, a casting temperature of 1442°C, a directional solidification cooling rate of 14.5°C / s, and an undercooling of 97°C, with the boride growth orientation of the Fe-B-Si alloy being
[002] ;
[0095] 2) Cut the directionally solidified Fe-B-Si alloy into 120*10*4mm pieces along the direction of directional solidification 3The test sample is then ground with a grinder and ultrasonically cleaned to remove wire cutting marks and oil stains on the sample;
[0096] 3) Place 10 kg of pure zinc into the zinc liquid corrosion device, set the program to raise the furnace temperature to 464 ° C, and keep it at this temperature for 120 minutes to completely melt the pure zinc;
[0097] 4) The treated test sample was fixed vertically on the sample holder of the zinc liquid corrosion device at a distance of 35mm from the center. The program was set to keep the zinc liquid temperature at 468℃, the motor drove the sample to rotate at a speed of 300r / min, and the sample moved at a speed of 7500mm / mm relative to the zinc liquid for 8 hours. Through the cross-sectional sample preparation, the in-situ generated three-layer Si-rich layer / FeZn 10 / FeZn 13 The thickness of the protective film is 91.5 μm.
[0098] Example 5
[0099] Preparation of Surface Protective Film on Fe-B-Si Alloy Resistant to Cavitation Erosion by High-Flow Zinc Liquid
[0100] The present invention selects pig iron, low-carbon ferrochrome, ferroboron, industrial pure iron and ferrosilicon alloy as raw materials.
[0101] 1) An Fe-B alloy was prepared by directional solidification. The composition of the Fe-B alloy, by weight, was 0.22% C, 3.55% B, 0.82% Cr, and 2.58% Si, with the remainder being Fe and unavoidable trace impurities. The alloy was prepared at a melting temperature of 1640°C, a casting temperature of 1450°C, a directional solidification cooling rate of 15.6°C / s, and a supercooling of 100°C. The Fe-B-Si alloy had a boride growth orientation in the
[002] direction.
[0102] 2) Cut the directionally solidified Fe-B-Si alloy into 120*10*4mm pieces along the direction of directional solidification 3 The test samples were then polished with a grinder and ultrasonically cleaned to remove wire cutting marks and oil stains on the samples.
[0103] 3) Place 10 kg of pure zinc into the zinc liquid corrosion device, set the program to raise the furnace temperature to 465 ° C, and keep it at this temperature for 120 minutes to completely melt the pure zinc;
[0104] 4) Fix the treated test sample vertically on the sample holder of the zinc liquid corrosion device at a distance of 35mm from the center. Set the program to keep the zinc liquid temperature at 470℃, the motor drives the sample to rotate at a speed of 300r / min, and the sample moves at a speed of 7500mm / mm relative to the zinc liquid for 10h. Figure 2As shown, the in-situ generated three-layer Si-rich layer / FeZn 10 / FeZn 13 The thickness of the protective film is 109.7 μm. Figure 3 The thickness of each protective film of directionally solidified Fe-B-Si alloy in zinc liquid is changed at different corrosion times. Figure 4 The corrosion rate of directionally solidified Fe-B-Si alloy changes with corrosion time.
[0105] Verification Example 1
[0106] Material type, thickness, structure testing and characterization of surface protection films
[0107] The samples were cold mounted with epoxy resin, and the mounting interface was polished with 400-1200# water-sandpaper and polished to a bright finish using diamond polish and canvas. The samples were cleaned with alcohol and dried, and finally characterized and examined using field emission scanning electron microscopy and energy spectrum analysis. The results are as follows:
[0108] 1) It was found that the protective film had a three-layer structure after 10 hours of corrosion, which played a protective role in the directionally solidified Fe-B-Si alloy: on the one hand, the protective film isolated the alloy from direct contact with the zinc liquid, inhibiting the diffusion of iron and zinc atoms, thereby reducing the corrosion rate; on the other hand, the protective film and the oriented boride were interlocked in a mortise and tenon structure, which was tightly bonded and not easy to fall off, thus preventing the outer layer of corrosion products from falling off and causing cavitation corrosion of the alloy;
[0109] 2) High-magnification observation of the interface of the protective film reveals three layers of film: a gray inner layer tightly adhered to the aggregate, a bright white second outer layer located between the oriented borides, and a bright white, smooth, columnar outermost layer tightly interlocked with the oriented borides near the alloy. Spectral mapping of the surface morphology of the sample after 8 hours of corrosion in liquid zinc reveals that the primary elements of the surface film are Fe, Zn, and Si.
[0110] 3) Multi-point EDS analysis was performed at different layers of the protective film, and the results were shown in Tables 1-3. According to the atomic ratio of different layers, the outermost layer Fe:Zn≈1:10, and the outermost layer Fe:Zn≈1:13, which proves that the silicon-rich layer is generated from the inside to the outside. 10 , FeZn 13 Three-layer protective film.
[0111] Table 1 Atomic percentage of elements in the innermost layer of the protective film
[0112]
[0113] Table 2 Atomic percentage of elements in the outer layer of the protective film
[0114]
[0115]
[0116] Table 3 Atomic percentage of elements in the outermost layer of the protective film
[0117]
[0118] 4) When the directionally solidified Fe-B-Si alloy is corroded in a dynamic zinc solution at 460℃, a silicon-rich protective layer is first formed on the corrosion interface, and then a columnar FeZn layer is formed outside the Si-rich layer. 13 , FeZn 13 Then react with the inner Si-rich layer to form FeZn 10 , eventually forming a silicon-rich layer, FeZn 10 、FeZn 13 Three-layer protective film, the reaction equation is as follows:
[0119] Fe(s)+Zn(l)→FeZn 13 (s)
[0120] FeZn 13 (s)+Fe(s)→FeZn 10 (s)
[0121] In summary, the present invention provides a directionally solidified Fe-B-Si alloy surface protective film and its preparation method. For the first time, a sample for zinc liquid cavitation is prepared using a relatively high silicon content. For the first time, a micron-scale three-layer Si-rich layer / FeZn layer is formed on the alloy surface in a flowing zinc liquid environment through chemical reaction. 10 / FeZn 13 The protective film avoids many disadvantages of manufacturing and developing new materials and coatings, and provides a new solution to the serious problem of cavitation erosion of parts in the hot-dip galvanizing industry.
[0122] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a surface protective film of a directionally solidified Fe-B-Si alloy, characterized in that: The following steps are involved: The Fe-B-Si alloy comprises C: 0.13-0.22%, B: 2.05-3.55%, Cr: 0.75-0.82%, Si: 2.42-2.58%, and the rest is Fe and inevitable trace impurities. The Fe-B-Si alloy prepared by the directional solidification process is placed in liquid zinc for interface reaction. The melting temperature of the directional solidification process is 1570-1640°C, and the casting temperature is 1420-1450°C. The directional solidification cooling rate is 10.2-15.6℃ / s, the supercooling degree is 95-100℃, the boride growth orientation of the directional solidified Fe-B-Si alloy is [002] direction, the angle with the corrosion interface is 90°, the temperature of the interface reaction is 460-470℃, the rotation speed of the Fe-B-Si alloy is controlled to be 300r / min, the reaction time is 2-10h, after the reaction is completed, after cooling, Si-rich layer / FeZn 10 / FeZn 13 The three layers of nested composite films form a mortise and tenon structure with the Fe2B skeleton, forming a composite protective film on the surface of the Fe-B-Si alloy that resists zinc liquid cavitation.
2. The method for preparing a surface protective film of a directionally solidified Fe-B-Si alloy according to claim 1, characterized in that: The specific interface reaction is as follows: the surface of the directionally solidified Fe-B-Si alloy is corroded and Si element is enriched, forming a Si-rich surface film between the Fe2B skeletons; the Fe atoms in the Si-rich surface film further diffuse and react with the high-temperature liquid zinc to form a columnar ζ-FeZn 13 protective film; subsequently generated ζ-FeZn 13 The protective film reacts with the Si-rich layer to form a layer of δ-FeZn between the two layers and between the Fe2B skeleton. 10 Protective film, δ-FeZn 10 The protective film grows in the shape of tree roots.
3. The method for preparing a surface protective film of a directionally solidified Fe-B-Si alloy according to claim 1 or 2, characterized in that: The thickness of the three-layer mortise and tenon structure protective film is 48.0 to 109.7 μm.
4. The method for preparing a surface protective film of a directionally solidified Fe-B-Si alloy according to claim 3, characterized in that: The innermost layer of the three-layer mortise and tenon structure is a Si-rich layer, and the FeZn 10 / FeZn 13 layer, the thickness of the Si-rich layer is 3.9 to 6.5 μm, FeZn 10 / FeZn 13 The thickness of the layer is 44.1 to 103.2 μm.
5. A directionally solidified Fe-B-Si alloy surface protective film, characterized in that: The surface protective film of the directional solidification Fe-B-Si alloy is prepared according to the method for preparing the surface protective film of the directional solidification Fe-B-Si alloy described in claim 1.
6. The directionally solidified Fe-B-Si alloy surface protective film according to claim 5, characterized in that: The cavitation rate of the protective film is 4.01~6.76μm / h.
Citation Information
Patent Citations
Cast Fe-B alloy resistant to zinc liquid cavitation erosion and preparation method of cast Fe-B alloy
CN111334723A
Directional solidification high-boron high-vanadium high-speed steel and production method thereof
CN113718160A